Cholesterol, Yield, Tibia and Clavicle Ash of Broilers fed High Available Phosphorus Corn and/or Phytase with/without Alum Litter Treatment - Miles , Dana M.; Junior, Philip A. Moore; Brooks, John P.; Smith, Douglas R.; Stilborn, Heather L.; Rice, David W.; Branton, Scott L. (International Journal of Poultry Science, 2019)
Objective: Three pen trials were conducted to assess the effects of the source of dietary phosphorus (P) on cholesterol, tibia and clavicle ash and yield in broilers raised on litter with and without alum addition. These are additional data to supplement a previous report on the main effect of alum addition to litter on the form of P in litter. Materials and Methods: A 2×2 factorial structure was used for the diets (subunit treatments) that included high available phosphorus/low phytate corn (HAPC) and phytase (PHYT). Results: Overall, there did not appear to be differences in breast cholesterol, thigh cholesterol, or yield when comparing alum vs. no alum litter treatment. In addition, breast tissue cholesterol was not affected by diet. For thigh cholesterol, HAPC was least when a difference was detected. The only differences in meat yield were in Trial 1, where the greatest were PHYT and yellow dent corn (YDC) at 71.55 and 71.26%, respectively. HAPC had the lowest yield at 70.43%. The meat yield for the combination diet of HAPC and PHYT (H and P) did not differ from any of the other diets (71.02%). Tibia ash only exhibited some differences in trial 2. For the alum treated pens at 6 weeks, HAPC had the greatest tibia ash with lower ash apparent for the other diets. Clavicle ash was only assessed in trial 2 and did not appear different among the treatments. In the previous study, alum addition reduced water soluble P for all diets but only H and P did so where alum was not added. In this report, marginally, HAPC had least cholesterol and greatest tibia ash but the lowest yield. Conclusion: It is concluded that the combination of diet, H and P, shows promise for sustainable broiler production by maintaining comparable cholesterol and meat yield as well as reducing excretion of water soluble P.